Measuring the zeta potential. The relationships with sandstone fineness - de Luxán, M. P.; Sánchez de Rojas, M. I.; Frías, M.; Patino, M. T. (Materiales de Construcción, 1989)
The application of the zeta potential technique in the area of construction materials and Portland cement is quite recent. The initial research work involved the study of cement suspensions or suspensions of one of the components of cement, such as alite, tricalcium alumínate, in the presence of additives and, more specifically, superplasticizers. The studies of this sort were extended with the mixing of active additions into cement (fly ashes, etc.). The present study discusses the application of siliceous materials (sandstone) as a basis of the research into the behaviour of sandstone mortars containing repair products.